DESIGN OF OBSTACLE AVOIDANCE SYSTEM ON HEXACOPTER USING VECTOR FIELD HISTOGRAM-PLUS METHOD - PURWITA SARY - NIM: 23215028 , INDRI
One technological solution in preventing human operator from direct exposure in the CRN (Chemical, Radioactive and Nuclear) contaminated area is to harness Unmanned Aerial Vehicle (UAV) to monitor the spread of such hazardous contaminant. Hexacopter is one of many alternative UAVs, which can be embedded with autonomous system. In order to be fully functional, the hexacopter must be equipped with obstacle avoidance subsystem which is considered to be essential to avoid any undesireable colisions. This thesis covers all details about how the hexacopter manage to determine the optimal track as to evade any collision from nearby objects. To implement such intelligent ability, VHF+ algorithm is opted as the base method in this research. This algoritm relies on local map in which the hexacopter has some information about current and target position without the need of prior knowledge about nearby condition (obstacle exact position). Lidar is used to sense the environment, which provides measurement on angle and radius of the objects around. Such sensor measurement is processed into 4 phases (grid histogram, primary polar histogram, binary polar histogram, masked polar histogram and steering). The obstacle avoidance subsystem is designed and implemented in a form of firmware embedded to the autonomous system of the hexacopter, which is tested in Software in The Loop Simulation (SILS). Simulation run on a computer with a processor frequency of 2.60 GHz. In Gazebo-ROS simulation, the hexacopter managed to avoid any obstacles with the safe range of ± 1.5 m and the average translation velocity was 0.4957m/s. The time cycle required to run VHF+ algorithm was 2.81 × 10s in which one cycle in guidance system needed 0.2384s.